Plasma processing of uranium-containing solid fuels: thermodynamic analysis and experiment - Messerle, V.Е.; Ustimenko, А.B.; Sitdikov, Zh.Zh.; Tastanbekov, A.K. (Recent Contributions to Physics, 2020)
This paper presents the results of thermodynamic and experimental studies of plasma processing of uranium-containing solid fuels on the example of Nizhne Illi brown coal with an ash content of 12% and Estonian dictionem shale with an ash content of 88%. The essence of plasma processing of uranium-containing solid fuel is to convert its organic mass into synthesis gas with simultaneous gasification of uranium-containing compounds and subsequent condensation of uranium-containing components from the gas phase. Thermodynamic analysis showed that at a temperature of 1800 K, the uranium-containing compounds completely pass into the gas phase in the form of uranium oxides. At this temperature, the gas phase of the products of plasma pyrolysis and steam gasification of solid fuels consists of more than 95% synthesis gas. Experiments on plasma pyrolysis and steam gasification of dictionem shales were conducted in a flow-type plasma reactor. In the case of plasma-steam gasification of shale, the yield of synthesis gas was 86%, the degree of carbon gasification was 70.4%, and the degree of uranium release into the gas phase was 83.6%. The results of the research show that the plasma processing technology is not susceptible to the quality of the fuels used. It is shown that the integral parameters of plasma gasification of uranium-containing fuels are higher than in their plasma pyrolysis.